Praktik Pembacaan Yasin Fadilah di Masyarakat Perspektif Living Qurâa>n dan Analisis Perubahan Sosial (Studi Kasus di Majelis Taklim Al-Muthmainnah Desa Lemahabang Kulon, Kecamatan Lemahabang, Kabupaten Cirebon) - Shobahah, Luthfiatus (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
This article focus on investigation about practice of reciting Al-Qurâan perspective of livingQuran and analysing social civilization. Living Quran is new approach for understanding sense of Quran with contextual concept. Practice of reciting Al-Qurâan which did by society is one of way to understand sense of Al-Qurâan. Research of living Quran be important because understanding and interpreting Al-Qurâan not only on library study facing texts of Al-Qurâan. Nevertheless, reception of society to practice of reciting Al-Qurâan is process an assembling and interpreting Al-Qurâan by context. Reception of Al-Qurâan theory and social civilization suitable for analysing of living Quran to find out social phenomenon related with presence of Al-Qurâan in certain community.Â Key Word : Living Quran, Social Civilization, Community.